Endovascular repair of type B acute aortic syndromes involving the left subclavian artery: A retrospective single-centre study - Mengyang Kang; Yang Zhao; Yan Meng; Qiang Ma; Junbo Zhang; Hao Qin; Hongyan Tian (PLoS ONE, 2025)
Background The mid-term outcomes of using the Castor single branched stent graft to treat patients with type B acute aortic syndromes (AASs) involving the left subclavian artery (LSA) were unclear. This study aims to evaluate the mid-term efficacy of the Castor single branched stent graft in the treatment of type B AASs involving the LSA. Methods The retrospective study enrolled patients with type B AASs involving the LSA who were consecutively admitted to our hospital between January 1, 2019 and October 30, 2023. Patients underwent thoracic endovascular aortic repair (TEVAR) using the Castor device. The clinical data of these patients were collected, and their outcomes were followed. Results This study included 106 patients, comprising those presenting with aortic dissection (AD) (n = 93), penetrating aortic ulcer (PAU) (n = 9), and intramural haematoma (IMH) (n = 4). All patients achieved the technical success. After a median follow-up period of 454 days (range: 359–771 days), all patients demonstrated survival, with 14 (14.4%) patients experiencing complications, including acute myocardial infarction (AMI, n = 1), endoleaks (n = 7), stenosis of the branched section(n = 3), stent graft-induced new entry tear (SINE, n = 2), and progressive aortic dilation (n = 1). Among the endoleaks, there were 1 Type Ib, 2 Type II, and 4 Type IV cases. Among the enrolled patients, two required re-intervention. No retrograde type A aortic dissection (RTAD), paraplegia or stroke were observed during the follow-up period. Conclusion The Castor device provided an easily manipulated, safe, and effective treatment option for patients with type B AASs involving the LSA.